2013
DOI: 10.2214/ajr.12.10375
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and System Factors Contributing to Diagnostic Errors in Radiology

Abstract: Every radiologist worries about missing a diagnosis or giving a false-positive reading. The retrospective error rate among radiologic examinations is approximately 30%, with real-time errors in daily radiology practice averaging 3-5%. Nearly 75% of all medical malpractice claims against radiologists are related to diagnostic errors. As medical reimbursement trends downward, radiologists attempt to compensate by undertaking additional responsibilities to increase productivity. The increased workload, rising qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
216
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(222 citation statements)
references
References 70 publications
2
216
0
4
Order By: Relevance
“…A possible deterrent to increasing the number of PAs worked by radiologists is reporting fatigue. It has been shown that problems such as visual fatigue and cognitive overload can result from reporting high volume and high-complexity images [22,23]. This can reduce productivity and increase stress levels in radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…A possible deterrent to increasing the number of PAs worked by radiologists is reporting fatigue. It has been shown that problems such as visual fatigue and cognitive overload can result from reporting high volume and high-complexity images [22,23]. This can reduce productivity and increase stress levels in radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue can also result in a decrease in the radiologist's working memory, particularly after several hours of continuous and prolonged decision making. The increased amount of effort (cognitive load) required to make an accurate diagnosis when tired can result in the radiologist taking short-cuts and subsequent diagnostic errors [31,32].…”
Section: Contributing Factors To Perceptual Errormentioning
confidence: 99%
“…A second, more focused and detailed search is performed after a specific clinical concern is articulated. This approach is thought to effectively utilize both systems of decision-making [32].…”
Section: Strategies For Error Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the European Society of Genitourinary Radiology (ESUR) guidelines, pelvic MR imaging should be performed to further characterize any sonographically indeterminate mass [ Clinical questions are always asked before the exam (including age, questions regarding clinical symptoms, hormonal status, hormonal medication, recent surgeries and recent deliveries).Cognitive biases such as anchoring and framing are reduced when the radiologist seeks more clinical information from patients, especially disconfirming information that disproves the initial clinical diagnosis [4] (Fig. 1).…”
Section: Mr Imaging Technique To Reduce Pitfalls In Imaging Indetermimentioning
confidence: 99%